(untitled) (International Journal of Environmental Sciences, 2025)
Soil Aquifer Treatment (SAT) has emerged as a significant method for the reuse of treated wastewater, leveraging natural filtration and biochemical processes during the percolation of effluent through unsaturated and saturated zones of the soil. This study aimed to investigate the effectiveness of SAT in removing various pollutants from primary and secondary treated sewage using a laboratory-scale soil column setup. The research focused on understanding the treatment performance, contaminant removal efficiency, and implications for full-scale SAT pond simulation. To achieve this, two identical soil columns were constructed, each with a length of 1000 mm and an internal diameter of 450 mm. The effective soil depth available for treatment was 700 mm. The experimental setup included a feeding tank, feeder assembly, distributor lines, and a pump to ensure a constant hydraulic loading rate (HLR) throughout the study. Two different types of sewage—primary treated and secondary treated—were fed separately into the two soil columns over a period of 90 days, simulating continuous SAT operations under controlled conditions. Throughout the experimental duration, samples were collected at regular intervals and analyzed for key water quality parameters. These included Suspended Solids (SS), Total Phosphorus (TP), Specific Conductance (SC), Nitrate-Nitrogen (NO₃-N), Chemical Oxygen Demand (COD), and Total Hardness (TH). The study revealed substantial pollutant removal across both soil columns. The soil matrix demonstrated significant efficacy in filtering and biologically transforming contaminants, especially under saturated and unsaturated flow conditions that mimic natural aquifer recharge processes. Notably, the results showed high removal efficiencies for Total Phosphorus and Total Suspended Solids, with removal rates reaching approximately 83% and 65%, respectively. These findings underscore the potential of SAT systems to effectively polish treated effluents, thereby reducing nutrient loads and suspended particulates before aquifer recharge or reuse applications. Additionally, considerable reductions in COD, nitrate nitrogen, and total hardness were observed, indicating the broader applicability of SAT in improving the physicochemical quality of reclaimed water. Overall, the study provides critical insights into the removal mechanisms of pollutants within the soil matrix and establishes the feasibility of using soil column experiments as predictive tools for the performance of full-scale SAT systems. The comparative evaluation of primary and secondary treated sewage further emphasizes the advantages of using higher quality effluents for maximizing treatment efficiency and ensuring environmental safety. These findings can inform future design and optimization strategies for SAT-based wastewater reuse systems in arid and semi-arid regions.